SPALAX NG: A breakthrough in radioxenon field measurement. (April 2018) - Cagniant, A.; Topin, S.; Le Petit, G.; Gross, P.; Delaune, O.; Philippe, T.; Douysset, G.
Abstract: Lessons-learned from 10 years of noble gas stations operation and dedicated R&D allowed the design of a New Generation of station. In order to produce 60 m 3 air equivalent Xenon samples every 8 h, it implements: (i) larger sampler unit for Xenon extraction (2 compressors and 8 nitrogen membranes), (ii) new noble gas adsorbent (Ag@ZSM5), (iii) hardened components and (iv) new high resolution coincidence low background spectrometer (HPGe/PIPSBox). Station expected radioxenon sensitivity is lower than 0.3 mBq/m 3 . Highlights: SPALAX stations have been in operation for 15 years. 5 years of dedicated R&D leaded to gas process and spectrometry upgrades. 3 month comparison between a R&D unit on a standard SPALAX station is given. Proving its higher sensitivity to radioxenon.